Chemical and bacteriological study of marine waters in the mouth of the Sin River - ديوب, رنيم; سـمر اختــيار; بــدر العــلي (Latakia University Journal -Biological Sciences Series, 2023)
This research is concerned with the study of some physical and chemical properties (temperature, salinity, electrical conductivity, pH, nitrite NO2, ammonium NH4, phosphate PO4) of Arab Al-Malik beach water. General germ count, total coliform, fecal coliform, and Streptococcus. The highest values of nutrient concentrations and bacteria counts were recorded during the summer season in July and June, which was accompanied by high temperature, pH values and salinity. The main reason may be due to the oil spill near the area in addition to human activities during that period. The chemical oxygen demand (COD) was also studied. The results showed a clear variation throughout the year, and the highest values were recorded in September.